2006
DOI: 10.1523/jneurosci.5199-05.2006
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Early Life Stress on [11C]DASB Positron Emission Tomography Imaging of Serotonin Transporters in Adolescent Peer- and Mother-Reared Rhesus Monkeys

Abstract: Peer-reared (PR) rhesus monkeys with early maternal separation later exhibit aggressiveness, impaired impulse control, alcohol abuse, and low CSF 5-hydroxyindoleacetic acid. This study compared regional brain serotonin transporter (SERT) binding between nine PR and seven mother-reared rhesus monkeys with [ 11 C]DASB positron emission tomography (PET) imaging. Parametric images of binding potential (BP) (which is proportional to B max /K D , in which B max is transporter density and K D is dissociation constant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
88
2
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(103 citation statements)
references
References 37 publications
11
88
2
2
Order By: Relevance
“…104 Using in vivo PET measures of 5-HT, studies involving the maternal separation paradigm have shown that, compared with mother-raised monkeys, juvenile monkeys exposed to early maternal deprivation have decreased SERT and 5-HT 1A binding in the raphe and frontal-limbic regions. 102,105 Taken together, these findings provide emerging evidence that exposure to stressors in early life could have a long-term effect on the 5-HT system.…”
Section: Adversity During Gestation and Childhood: Consequences For Bmentioning
confidence: 70%
See 1 more Smart Citation
“…104 Using in vivo PET measures of 5-HT, studies involving the maternal separation paradigm have shown that, compared with mother-raised monkeys, juvenile monkeys exposed to early maternal deprivation have decreased SERT and 5-HT 1A binding in the raphe and frontal-limbic regions. 102,105 Taken together, these findings provide emerging evidence that exposure to stressors in early life could have a long-term effect on the 5-HT system.…”
Section: Adversity During Gestation and Childhood: Consequences For Bmentioning
confidence: 70%
“…Maternal deprivation involves separating infants from their mothers at birth, hand-rearing them in a nursery for the first month, and then rearing them with same-age peers until 6 months of age, after which they would be moved into larger groups that also contain mother-reared age-mates and sometimes older adults. 102 Both peer-reared and mother-reared monkeys would then continue to live in these mixed social groups at least until puberty. With such monkey separation paradigms, it was shown that, in addition to several behavioural and emotional alterations (e.g., increased anxiety, impulsivity, and aggression 103 ), the monkeys who grew up with their peers had altered levels of the 5-HT metabolite 5-HIAA in the CSF, which remained stable over time, up to adulthood.…”
Section: Adversity During Gestation and Childhood: Consequences For Bmentioning
confidence: 99%
“…Studies on early maternal separation in peer-reared rhesus monkeys (an animal model which will be discussed in another section of this review), who later exhibited aggressive and impulsive behaviour, have reported loss of 5-Htt binding restricted in areas including the midbrain, thalamus, caudate, putamen and anterior cingulate cortex, but not the prefrontal cortex (Ichise et al 2006). neuroticism, a personality trait which may involve impulsivity, has been positively correlated with thalamic 5-Htt binding (takano et al 2007) and negatively associated with openness to values, the latter of which has shown a negative correlation with 5-Htt binding in subcortical regions (Kalbitzer et al 2009).…”
Section: Serotonin Transporter Imaging and Post-mortem Studies Of Suimentioning
confidence: 99%
“…they have lower levels of CSF 5-HIAA concentrations than mother-reared monkeys from early infancy to later adulthood (Shannon et al 2005;Higley and Suomi 2011) and have significantly different peripheral measures of neurotrophic factors nGF and BDnF (Cirulli et al 2009) and as adolescents and young adults consume significantly more alcohol than their mother-reared counterparts during a "happy hour" situation (Higley et al 1991;Fahlke et al 2002). neuroimaging studies have also shown the POreared monkeys to differ significantly in brain function and structure (Doudet et al 1995;Ichise et al 2006;Spinelli et al 2009). Finally, major differences have been found in genome-wide expression in leucocytes between PO-reared and mother-reared monkeys (Cole et al 2012).…”
Section: Animal Models Of Suicidementioning
confidence: 99%
“…This approach has been used extensively since its introduction [16][17][18][19]. Nevertheless, as with every reference approach, it does not allow for estimation of the V T and requires the existence of a reference region with little or no specific binding that does not differ between groups of interest, which is not available for all radioligands.…”
Section: Introductionmentioning
confidence: 99%